Relationship Banking, Liquidity, and Investment in the German Industrialization - Fohlin, Caroline (Journal of Finance, 1998)
Close bank relationships are thought to ameliorate firms' liquidity constraints—a phenomenon frequently measured by liquidity sensitivity of investment. Using German firms during the formative years of universal banking (1903–1913), this paper shows that, even controlling for selection bias, investment is more sensitive to internal liquidity for bank-networked firms than unattached firms. The firm exhibiting the greatest liquidity sensitivity, however, faced no apparent liquidity constraint. The findings yield two implications: they support recent research rejecting a linear relationship between liquidity sensitivity and financing constraints, and they suggest that relationship banking provides no consistent lessening of firms' liquidity sensitivity.